Social cognitions and smoking behaviour: Temporal resolution matters. Issue 1 (9th December 2019) - Brinken, Lillian; Schüz, Benjamin; Ferguson, Stuart G.; Scholz, Urte; Schüz, Natalie
Abstract : Objectives: Health behaviour theories outline how cognitions predict behaviours, but rarely specify the temporal relation between cognitions and behaviours. It is not known whether these predictive relationships vary depending on temporal resolution or whether the relative influence of cognitions varies with measurement schedules. The current exploratory study therefore investigates whether the associations between behavioural cognitions (self‐efficacy, intention, and risk perception) and smoking vary when measured momentarily, at day level, or using the more common baseline–follow‐up design. Design: EMA study involving 36 continuing smokers over 17 days. Participants logged cigarettes and reported their cognitions at baseline, daily (evening), and in response to momentary surveys. Methods: Random‐effects models were used to compare the effects of cognitions measured at different time points on (1) the number of cigarettes smoked daily and (2) the time interval until the next cigarette smoked. Results: Self‐efficacy and risk perception measured at baseline significantly predicted cigarettes smoked each day, but this effect became non‐significant when daily measurements of cognitions were included in the model. Momentary smoking behaviour was predicted by momentary measurements of risk perception, with no significant effects of social cognitions at baseline. Conclusions: Relationships between cognitions and behaviours vary according to the temporal resolution of the measurement schedule. Ensuring that the temporal resolution of assessment is appropriate for the temporal dynamics of the behaviour being assessed is important. Future research is needed to investigate the potential for leveraging specific cognitive processes depending on temporal importance in order to increase health‐promoting behaviours. Statement of contribution: What is already known on this subject? Social cognitions including intentions, risk perception, and self‐efficacy have been observed to predict smoking. Little is known about the role of time in the cognition–behaviour relationship. Cognitions have been observed to fluctuate, but instability is typically not considered in research design. What does this study add? Daily measurement of social cognitions predicts behaviour better than measurements taken at baseline. Momentary smoking behaviour is predicted by momentary cognitions at the intra‐individual level. Temporal resolution of measurement should be considered when investigating cognition–behaviour relationships.